(untitled) (Revista Latino-Americana de Enfermagem, 2008)
Qualitative research using a dialectics view; the objective is to analyze the demands and the expectations from the setting of managerial practices in view of the Pedagogical Project and the strategies which may or may not favor the transforming praxis. It involves 11 students, 12 professors, and 12 service nurses who are the participants in the teaching-learning process of managerial knowledge, in the interceding space, in the fields of practice and in the curricular training programs, both in the hospital environment and in the basic health services and of the Nursing graduation course from a Federal University, from the city of Alfenas-MG. It uses the collecting technique by focal group and the analysis of the contents is subsided by two great discussions: background and work. The results point that the nurse's background and praxis must go through the work processes in the caring, managerial and educative dimensions as well as in the scientific investigation, building paths for the development of competences, in the teaching and service interaction, following the current National Curriculum Guidelines.